Convergence Analysis of an Accelerated Iteration for Monotone Generalized α-Nonexpansive Mappings with a Partial Order - Yi-An Chen; Dao-Jun Wen (Journal of Function Spaces)
In this paper, we introduce a new accelerated iteration for finding a fixed point of monotone generalized α-nonexpansive mapping in an ordered Banach space. We establish some weak and strong convergence theorems of fixed point for monotone generalized α-nonexpansive mapping in a uniformly convex Banach space with a partial order. Further, we provide a numerical example to illustrate the convergence behavior and effectiveness of the proposed iteration process.